2020
DOI: 10.1109/access.2020.2993903
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Renewable Energy Project: A Technical Proposal for Rural Electrification to Local Communities

Abstract: The increasing environmental awareness across the globe is leading towards a green and clean world. Currently, Pakistan is going through an acute energy crisis; it is an ongoing challenge for the government to provide uninterrupted power supply at economical rates to its citizens and potential industrial investors, now and in future. Thus, this energy scenario necessitates the incorporation of renewable energy technologies with power systems to enhance its generation capacity, and to overcome electricity outag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Among alternative and renewable resources, wind power has been recognized as a significant potential source of renewable energy in Pakistan. The country has a total estimated gross wind power potential installable capacity of 346,000 MW [2]. In [3], authors have forecasted the realization of about 40-70% of Pakistan wind power potential by the year 2030.…”
Section: Wind Potential In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Among alternative and renewable resources, wind power has been recognized as a significant potential source of renewable energy in Pakistan. The country has a total estimated gross wind power potential installable capacity of 346,000 MW [2]. In [3], authors have forecasted the realization of about 40-70% of Pakistan wind power potential by the year 2030.…”
Section: Wind Potential In Pakistanmentioning
confidence: 99%
“…According to the NREL report of June 2007 named Wind Resource Assessment and Mapping for Afghanistan and Pakistan, by Dennis Elliott, Pakistan has a total land area of about 877525 km 2 in which installed capacity is MW per km 2 . Out of the entire land area, only 26362 km 2 land area is considered with percent windy area which equals 3.0% and the total capacity installed of 131800 MW [20].…”
Section: Wind Energy Potential Of Baluchistan Provincesmentioning
confidence: 99%
“…A new methodology is developed to identify the different configuration problems and maximize the techno-economic benefits of distribution systems for all envisaged cases and scenarios [12]. As well, other studies have identified the most convenient HRES option for the Public Library building, the hotel building, and other locations by evaluating the potential for energy sources in the proposed area using HOMER and a similar assessment tool [13][14][15][16][17][18]. When hybridizing energy sources, over one energy source in the system makes performance evaluation and decision-making complex and requires thorough technical, economic, and environmental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted by Wang and Yang by considering the comfort factors of thermal, visual, and air quality employing multi‐objective particle swarm optimization technique. Moreover, a graphical user interface (GUI) has been proposed in their extended work 9,10 . The three comfort parameters including thermal, visual, and air quality have been considered 11 for energy conservation and comfort management that employed multi‐islanded genetic algorithm (MIGA) and simple genetic algorithm (GA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a graphical user interface (GUI) has been proposed in their extended work. 9,10 The three comfort parameters including thermal, visual, and air quality have been considered 11 for energy conservation and comfort management that employed multi-islanded genetic algorithm (MIGA) and simple genetic algorithm (GA). The studies considered use fuzzy inference system for the local controller agents.…”
Section: Introductionmentioning
confidence: 99%